Zur Diskussion um die Erfolgswirkung der Wertstellungsgewinne - Kosfeld, Endrik (Credit and Capital Markets – Kredit und Kapital, 1980)
On the Debate concerning the Earnings Effect of Value-Date Profits Not only in connection with bank cost accounting, but also with respect to the price policy of the banks, which has been the subject of lively public debate in recent years, highly divergent views have been expressed in some instances concerning the level of “value-date” profits. Inter alia, this is probably attributable to the fact that, on the whole, the pointers in the literature concerning the calculation of value-date profits cannot be regarded as very convincing. In this article, for the calculation of value-date profits the payments with favourable value dates, subdivided into inpayments and outpayments, are examined on the basis of the money transfer transactions for their effect on the balance sheet. The effect of value-date profits on the profitability of a bank is shown by varying the value dates of payments and then comparing those payments’ effects on the balance sheet. The analysis is initially carried out solely for credit accounts, both with and without internal clearing; then, in a second step, the debit accounts are also included in the analysis. The selection of interest rates for amounts with favourable value dates reveals that the non-internally cleared outgoing payments and the internally cleared outgoing payments from debit accounts, and also the inpayments in favour of debit accounts have to be valued with an interest rate corresponding to the average interest rate for assets or the loan interest rate. From this it must be concluded that inpayments in favour of credit accounts make a relatively small contribution to earnings, on account of the applicable interest rate, than other payment transactions. Furthermore, the fluctuations in the interest level permit the conclusion that the contribution margins in payment transactions are also subject to marked fluctuations so that isolated consideration of contribution margins in payment transactions related to the whole year must be considered not very suitable as a basis for ...